2020
DOI: 10.1186/s42238-020-00055-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cannabidiol to citalopram in targeting fear memory in female mice

Abstract: Background Cannabidiol (CBD) and selective serotonin reuptake inhibitors (SSRIs) are currently used to treat post-traumatic stress disorder (PTSD). However, these drugs are commonly studied after dosing just prior to extinction training, and there are gaps in our understanding of how they affect fear memory formation, their comparative effects on various types of memory, and of sexual dimorphisms in effects. Also, more studies involving female subjects are needed to balance the gender-inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Recent data on the impacts of citalopram on learning and memory processes are inconsistent, as studies in mammals have shown contradictory results. Intriguingly, the memory impairments induced by citalopram are more likely to occur in normal or healthy mammalian models ,, but are conversely also present in disease models. Given our results (Figure S2) in the “”-maze and previous reports in the plus maze that demonstrated that zebrafish perform well in complex associative learning tasks, we investigated whether long-term exposure to citalopram resulted in decreased learning and memory in adult zebrafish. A significant decline in learning and memory performance was noted in citalopram-exposed adult zebrafish, with males and groups that received higher concentrations (10 and 100 μg/L) appearing relatively more vulnerable to impairment induced by long-term citalopram exposure.…”
Section: Resultsmentioning
confidence: 87%
“…Recent data on the impacts of citalopram on learning and memory processes are inconsistent, as studies in mammals have shown contradictory results. Intriguingly, the memory impairments induced by citalopram are more likely to occur in normal or healthy mammalian models ,, but are conversely also present in disease models. Given our results (Figure S2) in the “”-maze and previous reports in the plus maze that demonstrated that zebrafish perform well in complex associative learning tasks, we investigated whether long-term exposure to citalopram resulted in decreased learning and memory in adult zebrafish. A significant decline in learning and memory performance was noted in citalopram-exposed adult zebrafish, with males and groups that received higher concentrations (10 and 100 μg/L) appearing relatively more vulnerable to impairment induced by long-term citalopram exposure.…”
Section: Resultsmentioning
confidence: 87%
“…Long-term oral CBD treatment reduced freezing in the cue test of all females, regardless of the genotype. Although it is well established that acute systemic CBD can impair fear memory consolidation ( Han et al, 2022 ; Shallcross et al, 2019 ; review: Stern et al, 2018 ), including in female mice ( Montoya et al, 2020 ), effects of chronic CBD on fear memory have had limited investigation, and chronic CBD does not affect fear memory acquisition ( Cheng et al, 2014a ; 2014c ). Considering CBD-induced differences in freezing were very limited in this study, future research should consider evaluating the effects of long-term CBD on fear learning in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for serotonin's involvement in FE processes comes mainly from studies investigating the relationship between different SSRIs and FE learning. Most commonly prescribed antidepressants—fluoxetine, paroxetine, sertraline, and citalopram—have the ability to facilitate the extinction of conditioned fear (Karpova et al, 2011; Montoya et al, 2020; Pedraza et al, 2019; Popova et al, 2014) and restore impaired extinction learning induced by different stressors (Pereira‐Figueiredo et al, 2017; Regue et al, 2019; Uniyal et al, 2019). SSRI‐induced augmentation of FE was associated with enhanced NMDAR expression in the amygdala and hippocampus (Popova et al, 2014), increased AMPAR hippocampal signaling (Gottschalk et al, 2018), and altered levels of BDNF mRNA and protein in the amygdala (Karpova et al, 2011; Regue et al, 2019), cortex (Uniyal et al, 2019), and hippocampus (Karpova et al, 2011; Regue et al, 2019; Uniyal et al, 2019).…”
Section: Molecular Mechanisms Of Fear Extinctionmentioning
confidence: 99%